Generic and species richness of ant fauna in different provinces of Nepal (Hymenoptera: Formicidae) - Subedi, Indra Prasad (Nepalese Journal of Zoology, 2022)
Nepal, a part of the Himalayan biodiversity hotspot, has a high diversity of habitat and species. Its myrmecofaunal diversity and distribution, however, is little understood. Here, I summarize the provincial distribution of all named species of ants for the seven provinces of Nepal through a literature review and examination of materials available at museum and private collections. The distribution of Nepalese ants in each province reveals that Bagmati province has the highest known generic and species richness with 37 genera and 93 species, followed by Gandaki (32, 68), Province 1 (27, 55), Sudurpashchim (15, 15), Lumbini (12, 13), Madhesh (9, 11), and Karnali (5, 5). The four of the seven provinces, Sudurpashchim, Karnali, Lumbini, and Madhesh have been significantly under sampled in the country in terms of documented species richness. Although the figures cannot accurately represent the real species richness of each province, I hope that by highlighting the research gaps, it will encourage further investigation.